Endophytic phyllosphere fungi and nutrient cycling in terrestrial ecosystems - Saikkonen K; Mikola J; Helander M (INDIAN ACAD SCIENCES, 2022)
The importance of phyllosphere fungi to ecosystem functioning via soil processes has aroused increasing interest during the last decade. Here, we briefly review the current knowledge of how the foliar endophytic fungi and nutrient cycling interact. Recent findings suggest that endophytes may affect plant litter quality, organisms that control litter decomposition and the availability of nutrients in plant communities. However, the results obtained so far are highly variable. We attempt to integrate these observations with the knowledge of ecology and life-history strategies of endophytic fungi, and highlight general rules and gaps in our knowledge. Finally, we suggest testable hypotheses for future studies.